Home and the social worlds beyond: exploring influences in the lives of children of mothers with intellectual disability. (10th March 2017) - Collings, S.; Llewellyn, G.; Grace, R.
Abstract: Background: Mothers with intellectual disability are likely to raise their children in socially disadvantaged circumstances, and many face social isolation; however, the impact of a potentially restricted home context on children's social worlds has not been examined. This study was conducted to explore influences in the social worlds of children of mothers with intellectual disability from a child's perspective. Methods: Seven children aged 7 to 11 years took part in at least two semi‐structured interviews over a year. Narrative accounts of each child's social interactions were analysed to ascertain if a pattern was present across the group. Results: Home was found to influence the children's social interactions elsewhere by providing (or not) predictable routines and rules, and support from a significant adult other than a mother. Home environments were found to influence other social worlds by establishing a foundation for children's expectations about social interactions. Conclusions: The social worlds of school‐aged children of mothers with intellectual disability are shaped by influences in the home that cannot be attributed exclusively to having a parent with intellectual disability. Significant adults provide an important support role and can be fulfilled by social service workers when a family‐centred approach is applied.